Amidst the shadows of trees : a Holocaust child's survival in the Partisans - Brysk, Miriam M. (Thorndike, Maine : Center Point Large Print, 2014)
"A Holocaust child-survivor shares her memories of escaping from Lida Ghetto in Belarus with her parents and joining the Partisans in the Lipiczany Forest as part of the Jewish Resistance"--
Keywords: Brysk, Miriam M; Holocaust, Jewish (1939-1945) -- Belarus -- Lida -- Personal narrative; Jewish children in the Holocaust -- Belarus -- Biography; Jews -- Poland -- Biography; Jews -- Belarus -- Biography; World War, 1939-1945 -- Jewish resistance -- Belarus -- Biography; World War, 1939-1945 -- Underground movements -- Belarus -- Biography; Guerrillas -- Belarus -- Biography; Holocaust survivors -- Biography